Pendidikan IPS dalam Memperkuat Pendidikan Karakter di Era Digital - Mustika Mustika; Anggi Berlian Safitri; Heni Safitri; Chandra Purna Irawan; Yusawinur Barella (Jurnal Sadewa : Publikasi Ilmu Pendidikan, pembelajaran dan Ilmu Sosial, 2025)
In the digital era, major challenges arise from the rapid development of technology, which has a positive impact on easy access to information, but also provides negative aspects such as dependence on gadgets and exposure to inappropriate content. This affects the formation of students' character, which is vulnerable to the influence of foreign cultures and detrimental information. Therefore, character education needs to be improved, one of which is through learning Social Sciences (IPS) which has an important role in instilling moral and social values. This study uses a literature study method to explore various theories and practices in integrating digital technology in IPS learning to strengthen character education. The results of the study show that IPS learning can be optimized to shape character through the integration of values ​​such as responsibility, discipline, cooperation, and respect for diversity, both inside and outside the classroom. Instilling character values ​​through IPS is expected to produce a young generation who are not only academically intelligent, but also have a strong character to face challenges in the digital era.